Village of Howard resident survey report - Janke, James; Trechter, David (My University, 2013)
The purpose of the survey was to gather residents' opinions about the quality of services and land use in the Village.
52 p.
Keywords: City planning--Wisconsin--Howard; Land use--Wisconsin--Howard; Public opinion--Wisconsin--Howard; Howard (Wis.)--Surveys; Howard (Wis.); Howard, Wisconsin; Brown County, Wisconsin; Village of Howard comprehensive plan; Comprehensive plan; Comprehensive plan report; Community planning; Public opinion survey